Effectiveness and feasibility of family and peer challenge intervention with wearable technology on physical activity among middle schoolers in Utah: A pilot trial - Sunku Kwon; Yang Bai; Youngwon Kim; Ryan D. Burns; Timothy A. Brusseau; Wonwoo Byun (Preventive Medicine Reports)
Objective: To examine the preliminary effectiveness and feasibility of physical activity (PA) intervention in middle schoolers. Methods: This 6-week, multi-component PA intervention was conducted in Salt Lake City, Utah, between November 2021 and January 2022. The intervention included tracking daily PA using a wearable activity monitor, education on PA and health, weekly motivational videos, and group challenges within family or peer groups. Three classes from one public middle school (N = 75; 51 % girls, aged 12–13 years) were randomly allocated into the intervention (i.e., family or peer challenges) or control groups. Changes in daily activity time between pre- and post-intervention were assessed using ActiGraph accelerometers. The feasibility of the intervention was evaluated through measures of adherence, retention, and acceptability. Results: After the intervention, 51 (girls: 51 %; age: 13.0 ± 0.7) of all participants completed the entire study protocol. Linear mixed models showed no statistically significant differences between interventions and control in daily sedentary behavior and PA times. Adherence to the intervention was moderately high (> 60 %), with a retention of 68 %. We also observed high satisfaction with wearable technology (≥ 78 %) in middle school students. However, only 39 % of participants frequently used the mobile app for their group challenge. Conclusions: Wearable technology in PA intervention may be of interest to young adolescents but not effectively change youth PA behavior during a 6-week intervention. Further research with larger samples, longer intervention durations, and refined engagement strategies is required to more accurately evaluate the impact and feasibility of this intervention.